IMPLEMENTASI DAN PERBANDINGAN METODE ITERATIVE DEEPENING SEARCH DAN HELD-KARP PADA MANAJEMEN PENGIRIMAN PRODUK - Rahayuda, I Gede Surya; Santiari, Ni Putu Linda (Department of Information Systems, Institut Teknologi Sepuluh Nopember, 2018)
Good delivery route determination is required to make savings, both in terms of time, mileage and cost. To determine good delivery route, this study implemented the pathfinding method. The program is created in two forms, the first form is using Iterative Deepening Search while the second form is using Karp Held. Sampel data used in this study is addresses of each place that frequently visited in product shipping. In addition, data of mileage, time and cost required on each trip also included. Data tes that used in this study are some addresses or locations that might be visited on product shipping. Data tests are tested on Held-Karp program and also on Iterative Deepening Search. From the experiments, the result show that Held-Karp method can determine better delivery route compared to Iterative Deepening Search. Total difference of Iterative Deepening Search and Held-Karp methods based on distance is 11,35 km, based on time is 27 minutes, and based on cost is 12,051 IDR. Overall, the difference of both methods is 19,66%.